The essence of analysis and verification methods in internal audit processes and the importance of information sources in them - Murodjon Shukurovich Mamatkulov; Saitmurat Masharip oglu Saitmuratov (THE INNOVATION ECONOMY, 2026)
This article studies the essence of the analysis and verification methods used in internal audit processes and the importance of information sources in these methods from a scientific and practical perspective. During the study, the effectiveness of analysis and verification approaches was assessed using the example of internal audits conducted in the public sector, in particular, in the Pension Fund system. The article reveals the role of methods such as recalculation, documentary comparison, trend analysis, interviews and observation in revealing identified financial deficiencies and overpayments. It also substantiates the impact of the legal status, reliability level and information value of information sources used in the audit process on the quality of audit evidence. The results of the study show that strengthening analytical approaches in internal audit and prioritizing information sources increases audit effectiveness.